South African art, the romantic principle and the Grahamstown group - Clark, George Phillip Haven (Rhodes University, Faculty of Humanities, Department of Fine Art, 1977)
The purpose of this essay is to examine the "rumblings in the belly of Leviathan from which we are able to diagnose his disease" (Comfort). Adopting a cyclical idea of art, it aims to point out that South African art has degenerated to a state where the much publicised so-called leaders of art are simply using charm techniques to woo the consent of a society whose metaphysics are derived from twentieth century collective materialism. The South African situation is examined, as is the Romantic principle underlying all genuine artistic activity. It is proposed that the cure lies in a reinstatement of this principle and in a readjustment of the concepts of reality and unreality. Finally, the Grahamstown Group is propounded as an embodiment of the Romantic principle with its implicit concept of artistic reality.
Keywords: Art, -- South African; Art -- South Africa -- Grahamstown